Preparation of high-strength, comfortable and durable antibacterial fiber for hotels

By esterifying biocarbon quantum dots with cotton fibers and adding polyester fibers, the problems of reduced antibacterial effect and insufficient breathability of hotel supplies fibers are solved, and long-lasting and effective antibacterial performance and strength improvement are achieved.

CN119771313AInactive Publication Date: 2025-04-08JIANGSU YAGAO HOTEL SUPPLIES CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411942101.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The antibacterial effect of existing hotel fibers has decreased after high-frequency washing, and the breathability and comfort are insufficient.

Method used

Biocarbon quantum dots are used to conduct esterification reactions with cotton fibers to form stable covalent bonds, making the carbon quantum dots firmly solid and fabrics, and polyester fibers are added to improve strength.

Benefits of technology

The antibacterial properties of the fiber are significantly improved, so that its antibacterial effect is basically maintained after 50 washes, and the strength and comfort of the fiber are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771313A_ABST
    Figure CN119771313A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of high-strength, comfortable and durable antibacterial fiber for hotels, which relates to the technical field of fiber preparation, including a shell of a reactor, a stirring device installed in the middle of the shell, a grinding device installed at the upper end of the shell, and a bubbling device installed inside the shell. The raw material biomass wormwood used in the invention is rich in source, low in price, high in carbon content, and as a natural antibacterial agent, it is highly safe, not easy to produce drug resistance, has no toxic side effects on the human body, and is easily degraded; covalent bonding makes the antibacterial performance lasting and effective.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fiber preparation, and in particular to the preparation of high-strength, comfortable and durable antibacterial fiber for hotels. Background Art

[0002] The higher the degree of globalization of the economy, the more people will need to stay in hotels for work, travel and other reasons. With the rapid economic growth and the improvement of consumption levels, people have higher and higher requirements for the quality of hotel linens. Cotton products are of superior quality, have greater resistance to alkali, are very comfortable to use, absorb sweat and are soft and comfortable, which is conducive to the "breathing" of sweat glands and human health, and are soft to the touch, making it easy to create a sleeping atmosphere. Therefore, cotton products have become the main choice of the hotel industry. On the other hand, cotton fabrics are also a good medium for nourishing microorganisms. Under the right temperature, humidity and corresponding nutrients, microorganisms can grow and reproduce rapidly. Cotton fabrics can easily absorb the excretions secreted by human sweat glands and spleen glands, providing the necessary nutrients for microorganisms. At the same time, high strength and multiple washing require hotel supplies to have excellent strength.

[0003] Carbon quantum dots (CQDs) are a new type of material that has attracted widespread attention in recent years. They usually refer to spherical carbon nanomaterials with a diameter of less than 10nm, which are composed of a sp2 / sp3 carbon core and an outer layer of oxygen / nitrogen functional groups. CQDs have similar fluorescence properties, electrochemical properties and photocatalytic capabilities to traditional semiconductor quantum dots, but they also overcome the poor biocompatibility and biotoxicity of traditional quantum dots. In addition, they have abundant raw material sources and simple preparation methods. They are a research hotspot in the fields of medicine, biological sciences, and materials science.

[0004] Chinese patent CN 117721560 A discloses a method for preparing a washing-resistant antibacterial nylon composite fabric, which includes roughening nylon fibers and fixing copper nanoparticles on the nylon fibers; washing and drying wool fibers and hemp fibers, and wrapping quaternary ammonium salts on the hemp fibers; blending nylon fibers with wool fibers and hemp fibers, and having a bacterial survival rate of 5%. However, the antibacterial effect was reduced by 10% after 10 washes, and the air permeability and comfort of the nylon fabric were poor. Summary of the invention

[0005] The purpose of the present invention is to solve the above-mentioned problems and to propose a preparation method of high-strength, comfortable and durable antibacterial fiber for hotels.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme: comprising a shell of a reaction kettle, a stirring device is installed in the middle of the shell, a grinding device is installed at the upper end of the shell, and a bubbling device is installed inside the shell;

[0007] The grinding device includes an outer cylinder fixedly installed at the upper end of the housing. A rotating shaft is rotatably installed at the middle position of the outer cylinder. A first motor is installed at the middle position of the outer wall of the upper end of the outer cylinder. The output shaft of the first motor is fixedly connected to the upper end of the rotating shaft. An air suction component is installed at the upper end of the rotating shaft. A rotating body is installed at the lower end of the rotating shaft. A grinding body for cooperating with the rotating body is installed at the lower end of the outer cylinder. A feed port is opened at the upper end of the outer cylinder. A sealing cover is installed at the upper end of the feed port. The grinding body is fixedly connected to the rotating shaft;

[0008] The rotating shaft includes an upper main shaft connected to the output shaft of the first motor. The lower end of the upper main shaft is rotatably installed with a lower main shaft. A one-way bearing is arranged between the upper main shaft and the lower main shaft. The upper main shaft and the lower main shaft are rotatably connected to the rotating body. The rotating body can be detachably made;

[0009] A chute is opened inside the rotating body. A slider for cooperating with the chute is fixedly installed on the outer wall of the lower main shaft. The chute is inclined;

[0010] In practical applications, when it is necessary to crush wormwood, first put the wormwood into the inner part of the outer cylinder from the feed port. Then the sealing cover is closed, and the first motor starts to work. The output shaft of the first motor drives the upper main shaft to rotate. The upper main shaft drives the lower main shaft. Then the lower main shaft drives the rotating body to rotate. The wormwood is ground between the rotating body and the grinding body. Then the wormwood falls between the rotating body and the grinding body, so as to crush the wormwood for convenient subsequent operations.

[0011] Further, the air suction component includes a protective shell fixedly installed at the middle position of the upper end of the outer cylinder. An air cylinder is fixedly installed on one side outer wall of the protective shell. Sealing plates are respectively fixedly arranged at both ends inside the air cylinder. A first air hole is opened at the middle position of the sealing plate far from the protective shell. A first one-way valve is installed inside the first air hole. A piston is slidably installed at the middle position of the air cylinder. A return spring is installed between the piston and the sealing plate with a one-way valve. An air outlet hole is opened at the limit distance of the piston. A second air hole is opened on the outer wall of the piston. A second one-way valve is installed inside the second air hole. A guide rod is fixedly installed at one end of the piston close to the protective shell. An elliptical disc for cooperating with the guide rod is fixedly arranged on the outer wall of the rotating shaft;

[0012] The bubbling device includes an annular exhaust pipe fixedly installed at the lower end of the housing. A U-shaped pipe is fixedly communicated with one side of the annular exhaust pipe. The upper end of the U-shaped pipe is communicated with the outer cylinder;

[0013] In practical applications, when all the wormwood inside the outer cylinder has completely fallen off, the rotating body will fall under the action of gravity, thus forming a seal between the grinding body and the rotating body. Subsequently, the first motor rotates in reverse, the output shaft of the first motor drives the upper main shaft to rotate, the upper main shaft drives the elliptical disk to rotate, the elliptical disk drives the guide rod to move reciprocally. Subsequently, gas enters from one end of the air cylinder, flows out from the air outlet holes, then enters the U-shaped pipe, and finally enters the annular exhaust pipe.

[0014] Furthermore, the stirring device includes a second motor, a stirring shaft, and stirring blades. The stirring blades are provided in multiple layers, the stirring blades are inclined, and the inclination directions of each layer of stirring blades are opposite.

[0015] Example 1

[0016] (1) Weigh 5 g of washed and dried wormwood, cut it into pieces, add 50 mL of deionized water and 0.5 mL of ethylenediamine, mix well, and transfer it to a polytetrafluoroethylene reaction kettle.

[0017] (2) React in an oven at 180 °C for 8 h. After the reaction is completed, cool to room temperature, centrifuge, and filter the insoluble substances. Freeze-dry the solution to obtain brown carbon quantum dot powder.

[0018] (3) Add carbon quantum dots to water to obtain a mass fraction of 5%, and a mass fraction of chitosan of 30%. Mix well and set aside.

[0019] (4) Immerse the cotton-polyester core-spun yarn in the above mixed solution, heat to 60 °C, and ultrasonicate for 2 h. After taking it out, dry it at 60 °C, wash and dry it.

[0020] Example 2

[0021] (1) Weigh 5 g of washed and dried wormwood, cut it into pieces, add 50 mL of deionized water and 0.5 mL of ethylenediamine, mix well, and transfer it to a polytetrafluoroethylene reaction kettle.

[0022] (2) React in an oven at 180 °C for 8 h. After the reaction is completed, cool to room temperature, centrifuge, and filter the insoluble substances. Freeze-dry the solution to obtain brown carbon quantum dot powder.

[0023] (3) Add carbon quantum dots to water to obtain a mass fraction of 8%, and a mass fraction of chitosan of 30%. Mix well and set aside.

[0024] (4) Immerse the cotton-iterative polyester core-spun yarn in the above mixed solution, heat to 60 °C, and ultrasonicate for 2 h. After taking it out, dry it at 60 °C, wash and dry it.

[0025] Example 3

[0026] (1) Weigh 5 g of washed and dried mugwort, chop it into pieces, add 50 mL of deionized water and 0.5 mL of ethylenediamine, mix well, and transfer it to a polytetrafluoroethylene reactor.

[0027] (2) The reaction was carried out in an oven at 180°C for 8 hours, and after the reaction was completed, the reaction was cooled to room temperature, centrifuged, and the insoluble matter was filtered out. The solution was freeze-dried to obtain brown carbon quantum dot powder.

[0028] (3) Add carbon quantum dots to water to obtain a mass fraction of 10% and chitosan to obtain a mass fraction of 30%, mix well and set aside.

[0029] (4) Immerse the cotton-polyester-cotton blended core-spun yarn in the above mixed solution, heat to 60°C, and ultrasonicate for 2 hours. After taking it out, dry it at 60°C, and then wash and dry it.

[0030] Example 4

[0031] (1) Weigh 5 g of washed and dried mugwort, chop it into pieces, add 50 mL of deionized water and 0.5 mL of ethylenediamine, mix well, and transfer it to a polytetrafluoroethylene reactor.

[0032] (2) The reaction was carried out in an oven at 180°C for 8 hours, and after the reaction was completed, the reaction was cooled to room temperature, centrifuged, and the insoluble matter was filtered out. The solution was freeze-dried to obtain brown carbon quantum dot powder.

[0033] (3) Add carbon quantum dots to water to obtain a mass fraction of 10% and chitosan to obtain a mass fraction of 30%, mix well and set aside.

[0034] (4) Immerse the cotton-polyester-cotton interwoven core-spun yarn in the above mixed solution, heat to 60°C, and ultrasonicate for 2 hours. After taking it out, dry it at 60°C, and then wash and dry it.

[0035] Comparative Example

[0036] The difference between Comparative Example 1 and the embodiment is that the textile fiber is not treated with carbon quantum dots on its surface.

[0037] The difference between Comparative Example 2 and Example 1 is that the material is not core-spun yarn but cotton fiber.

[0038] The antibacterial properties of the textiles obtained in Examples 1 to 4 and Comparative Example 1 were tested. Antibacterial performance test: Determined in accordance with GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method". Antibacterial effect washability test: Washed in accordance with the test condition A1M in GB / T 12490-2014. By comparison, it can be seen that wormwood carbon quantum dots can effectively improve the antibacterial properties of the fiber, and the higher the concentration, the better the effect. After washing 50 times, its antibacterial properties did not change much, indicating that the bond was relatively strong; the breaking strength test of Examples 1 to 4 and Comparative Example 2 was carried out, and the strength was improved by adding polyester fiber.

[0039] Table 1 Antibacterial performance test results (unit: %)

[0040]

[0041]

[0042] Table 2 Strength test results (unit: cN / tex)

[0043]

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] The principle of this technology is: (1) Bio-carbon quantum dots contain abundant carboxyl and hydroxyl groups, which react with the cotton fibers in the core-spun yarn during the drying process to form stable covalent bonds, making the carbon quantum dots firmly fixed to the fabric; (2) the polyester fibers provide support for the fabric strength;

[0046] The raw material biomass wormwood used in the present invention is abundant in source, low in price, high in carbon content, and as a natural antibacterial agent, it is highly safe, not prone to drug resistance, has no toxic side effects on the human body, and is easily degraded; covalent bonding makes the antibacterial property lasting and effective. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a preparation process diagram of a high-strength, comfortable and durable antibacterial fiber for hotels proposed by the present invention;

[0048] Figure 2 This is a schematic diagram of a preparation device for preparing a high-strength, comfortable and durable antibacterial fiber for hotels proposed by the present invention;

[0049] Figure 3 This is a schematic diagram of a grinding device for preparing a high-strength, comfortable and durable antibacterial fiber for hotels proposed by the present invention;

[0050] Figure 4 This is a schematic diagram of an air intake component for preparing a high-strength, comfortable and long-lasting antibacterial fiber for hotels proposed by the present invention;

[0051] Figure 5 A schematic diagram of a rotating body for preparing a high-strength, comfortable and durable antibacterial fiber for hotels proposed by the present invention;

[0052] Figure 6 This is a schematic diagram of a rotating shaft for preparing a high-strength, comfortable and durable antibacterial fiber for hotels proposed by the present invention.

[0053] In the figure: 1. Outer shell; 2. Stirring device; 3. Bubbling device; 301. C-shaped pipe; 302. Annular exhaust pipe; 4. Grinding device; 401. Outer cylinder; 402. Feed inlet; 403. First motor; 405. Suction assembly; 4051. Protective shell; 4052. Air cylinder; 4053. Sealing plate; 4054. Elliptical disk; 4055. Piston; 4056. Return spring; 4057. Guide rod; 406. Rotating body; 4061. Chute; 407. Grinding body; 408. Rotating shaft; 4081. Upper main shaft; 4082. Lower main shaft; 4083. Slide block. Detailed implementation manner

[0054] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.

[0055] In the description of the present invention, it should be understood that the orientation or positional relationship indicated by the terms "upper", "lower", "front", "rear", "left", "right", "top", "bottom", "inner", "outer", etc. is based on the orientation or positional relationship shown in the accompanying drawings, and is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be construed as a limitation to the present invention.

[0056] Refer to Figure 1-6 , the preparation of a high-strength, comfortable and long-lasting antibacterial fiber for hotels, including the outer shell 1 of the reaction kettle, a stirring device 2 is installed in the middle position of the outer shell 1, a grinding device 4 is installed at the upper end of the outer shell 1, and a bubbling device 3 is installed inside the outer shell 1;

[0057] The grinding device 4 includes an outer cylinder 401 fixedly installed at the upper end of the outer shell 1, a rotating shaft 408 is rotatably installed in the middle position of the outer cylinder 401, a first motor 403 is installed in the middle position of the outer wall at the upper end of the outer cylinder 401, the output shaft of the first motor 403 is fixedly connected to the upper end of the rotating shaft 408, a suction assembly 405 is installed at the upper end of the rotating shaft 408, a rotating body 406 is installed at the lower end of the rotating shaft 408, a grinding body 407 cooperating with the rotating body 406 is installed at the lower end of the outer cylinder 401, a feed inlet 402 is opened at the upper end of the outer cylinder 401, a sealing cover is installed at the upper end of the feed inlet 402, and the grinding body 407 is fixedly connected to the rotating shaft 408;

[0058] The rotating shaft 408 includes an upper main shaft 4081 connected to the output shaft of the first motor 403. A lower main shaft 4082 is rotatably installed at the lower end of the upper main shaft 4081. A one-way bearing is provided between the upper main shaft 4081 and the lower main shaft 4082. The upper main shaft 4081 and the lower main shaft 4082 are rotatably connected to the rotating body 406, and the rotating body 406 can be detachably made;

[0059] A chute 4061 is formed inside the rotating body 406. A slider 4083 for cooperating with the chute 4061 is fixedly installed on the outer wall of the lower main shaft 4082, and the chute 4061 is inclined;

[0060] In practical applications, when it is necessary to crush wormwood, the wormwood is first put into the inner part of the outer cylinder 401 from the feed port 402. Then the sealing cover is closed, and the first motor 403 starts to work. The output shaft of the first motor 403 drives the upper main shaft 4081 to rotate. The upper main shaft 4081 drives the lower main shaft 4082, and then the lower main shaft 4082 drives the rotating body 406 to rotate. The wormwood is ground between the rotating body 406 and the grinding body 407, and then the wormwood falls between the rotating body 406 and the grinding body 407, so as to crush the wormwood for convenient subsequent operations.

[0061] Further, the air suction assembly 405 includes a protective shell 4051 fixedly installed at the middle position of the upper end of the outer cylinder 401. An air cylinder 4052 is fixedly installed on one outer wall of the protective shell 4051. Sealing plates 4053 are respectively fixedly arranged at both ends inside the air cylinder 4052. A first air hole is formed at the middle position of the sealing plate 4053 far from the protective shell 4051. A first one-way valve is installed inside the first air hole. A piston 4055 is slidably installed at the middle position of the air cylinder 4052. A return spring 4056 is installed between the piston 4055 and the sealing plate 4053 with a one-way valve. An air outlet hole is formed at the limit distance of the piston 4055. A second air hole is formed on the outer wall of the piston 4055. A second one-way valve is installed inside the second air hole. A guide rod 4057 is fixedly installed at one end of the piston 4055 close to the protective shell 4051. An elliptical disc 4054 for cooperating with the guide rod 4057 is fixedly arranged on the outer wall of the rotating shaft 408;

[0062] The bubbling device 3 includes an annular exhaust pipe 302 fixedly installed at the lower end of the housing 1. A C-shaped pipe 301 is fixedly communicated with one side of the annular exhaust pipe 302, and the upper end of the C-shaped pipe 301 is communicated with the outer cylinder 401;

[0063] In practical applications, when all the wormwood inside the outer cylinder 401 has completely fallen off, the rotating body 406 will fall under the action of gravity, so that a seal is formed between the grinding body 407 and the rotating body 406. Subsequently, the first motor 403 rotates in reverse, the output shaft of the first motor 403 drives the upper main shaft 4081 to rotate, the upper main shaft 4081 drives the elliptical disk 4054 to rotate, the elliptical disk 4054 drives the guide rod 4057 to move reciprocally. Subsequently, gas enters from one end of the air cylinder 4052, flows out from the air outlet holes, then enters the U-shaped pipe 301, and finally enters the annular exhaust pipe 302.

[0064] Further, the stirring device 2 includes a second motor, a stirring shaft and stirring blades. The stirring blades are provided in multiple layers, the stirring blades are inclined, and the inclination directions of each layer of stirring blades are opposite.

[0065] Example 1

[0066] (1) Weigh 5 g of washed and dried wormwood, cut it into pieces, add 50 mL of deionized water and 0.5 mL of ethylenediamine, mix well, and transfer it to a polytetrafluoroethylene reaction kettle.

[0067] (2) React in an oven at 180 °C for 8 h. After the reaction is completed, cool to room temperature, centrifuge, and filter the insoluble substances. Freeze-dry the solution to obtain a brown carbon quantum dot powder.

[0068] (3) Add carbon quantum dots to water to obtain a mass fraction of 5%, and a mass fraction of chitosan of 30%. Mix well and set aside.

[0069] (4) Immerse the cotton-polyester core-spun yarn in the above mixed solution, heat to 60 °C, and ultrasonicate for 2 h. After taking it out, dry it at 60 °C, wash and dry it.

[0070] Example 2

[0071] (1) Weigh 5 g of washed and dried wormwood, cut it into pieces, add 50 mL of deionized water and 0.5 mL of ethylenediamine, mix well, and transfer it to a polytetrafluoroethylene reaction kettle.

[0072] (2) React in an oven at 180 °C for 8 h. After the reaction is completed, cool to room temperature, centrifuge, and filter the insoluble substances. Freeze-dry the solution to obtain a brown carbon quantum dot powder.

[0073] (3) Add carbon quantum dots to water to obtain a mass fraction of 8%, and a mass fraction of chitosan of 30%. Mix well and set aside.

[0074] (4) Immerse the cotton-polyester iterative core-spun yarn in the above mixed solution, heat to 60 °C, and ultrasonicate for 2 h. After taking it out, dry it at 60 °C, wash and dry it.

[0075] Example 3

[0076] (1) Weigh 5 g of washed and dried mugwort, chop it into pieces, add 50 mL of deionized water and 0.5 mL of ethylenediamine, mix well, and transfer it to a polytetrafluoroethylene reactor.

[0077] (2) The reaction was carried out in an oven at 180°C for 8 hours, and after the reaction was completed, the reaction was cooled to room temperature, centrifuged, and the insoluble matter was filtered out. The solution was freeze-dried to obtain brown carbon quantum dot powder.

[0078] (3) Add carbon quantum dots to water to obtain a mass fraction of 10% and chitosan to obtain a mass fraction of 30%, mix well and set aside.

[0079] (4) Immerse the cotton-polyester-cotton blended core-spun yarn in the above mixed solution, heat to 60°C, and ultrasonicate for 2 hours. After taking it out, dry it at 60°C, and then wash and dry it.

[0080] Example 4

[0081] (1) Weigh 5 g of washed and dried mugwort, chop it into pieces, add 50 mL of deionized water and 0.5 mL of ethylenediamine, mix well, and transfer it to a polytetrafluoroethylene reactor.

[0082] (2) The reaction was carried out in an oven at 180°C for 8 hours, and after the reaction was completed, the reaction was cooled to room temperature, centrifuged, and the insoluble matter was filtered out. The solution was freeze-dried to obtain brown carbon quantum dot powder.

[0083] (3) Add carbon quantum dots to water to obtain a mass fraction of 10% and chitosan to obtain a mass fraction of 30%, mix well and set aside.

[0084] (4) Immerse the cotton-polyester-cotton interwoven core-spun yarn in the above mixed solution, heat to 60°C, and ultrasonicate for 2 hours. After taking it out, dry it at 60°C, and then wash and dry it.

[0085] Comparative Example

[0086] The difference between Comparative Example 1 and the embodiment is that the textile fiber is not treated with carbon quantum dots on its surface.

[0087] The difference between Comparative Example 2 and Example 1 is that the material is not core-spun yarn but cotton fiber.

[0088] The antibacterial properties of the textiles obtained in Examples 1 to 4 and Comparative Example 1 were tested. Antibacterial performance test: Determined in accordance with GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method". Antibacterial effect washability test: Washed in accordance with the test condition A1M in GB / T 12490-2014. By comparison, it can be seen that wormwood carbon quantum dots can effectively improve the antibacterial properties of the fiber, and the higher the concentration, the better the effect. After washing 50 times, its antibacterial properties did not change much, indicating that the bond was relatively strong; the breaking strength test of Examples 1 to 4 and Comparative Example 2 was carried out, and the strength was improved by adding polyester fiber.

[0089] Table 1 Antibacterial performance test results (unit: %)

[0090]

[0091]

[0092] Table 2 Strength test results (unit: cN / tex)

[0093]

[0094] Compared with the prior art, the present invention has the following beneficial effects:

[0095] The principle of this technology is: (1) Bio-carbon quantum dots contain abundant carboxyl and hydroxyl groups, which react with the cotton fibers in the core-spun yarn during the drying process to form stable covalent bonds, making the carbon quantum dots firmly fixed to the fabric; (2) the polyester fibers provide support for the fabric strength;

[0096] The raw material biomass wormwood used in the present invention is abundant in source, low in price, high in carbon content, and as a natural antibacterial agent, it is highly safe, not prone to drug resistance, has no toxic side effects on the human body, and is easily degraded; covalent bonding makes the antibacterial property lasting and effective.

[0097] The above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A preparation method for high-strength, comfortable and durable antibacterial fiber for hotels, characterized in that: It includes the outer shell (1) of a reaction kettle. A stirring device (2) is installed at the middle position of the outer shell (1). A grinding device (4) is installed at the upper end of the outer shell (1). A bubbling device (3) is installed inside the outer shell (1). The grinding device (4) includes an outer cylinder (401) fixedly installed at the upper end of the outer shell (1). A rotating shaft (408) is rotatably installed at the middle position of the outer cylinder (401). A first motor (403) is installed at the middle position of the outer wall at the upper end of the outer cylinder (401). The output shaft of the first motor (403) is fixedly connected to the upper end of the rotating shaft (408). An air suction component (405) is installed at the upper end of the rotating shaft (408). A rotating body (406) is installed at the lower end of the rotating shaft (408). A grinding body (407) for cooperating with the rotating body (406) is installed at the lower end of the outer cylinder (401). A feed inlet (402) is opened at the upper end of the outer cylinder (401). A sealing cover is installed at the upper end of the feed inlet (402).

2. The preparation method of a high-strength, comfortable and durable antibacterial fiber for hotels according to claim 1, characterized in that: The air suction component (405) includes a protective shell (4051) fixedly installed at the middle position of the upper end of the outer cylinder (401). An air cylinder (4052) is fixedly installed on one side outer wall of the protective shell (4051). Sealing plates (4053) are respectively fixedly arranged at both ends inside the air cylinder (4052). A first air hole is opened at the middle position of the sealing plate (4053) far from the protective shell (4051). A first one-way valve is installed inside the first air hole. A piston (4055) is slidably installed at the middle position of the air cylinder (4052). A return spring (4056) is installed between the piston (4055) and the sealing plate (4053) with a one-way valve. An air outlet hole is opened at the limit distance of the piston (4055). A second air hole is opened on the outer wall of the piston (4055). A second one-way valve is installed inside the second air hole. A guide rod (4057) is fixedly installed at one end of the piston (4055) close to the protective shell (4051). An elliptical disc (4054) for cooperating with the guide rod (4057) is fixedly arranged on the outer wall of the rotating shaft (408).

3. The preparation method of a high-strength, comfortable and durable antibacterial fiber for hotels according to claim 2, characterized in that: The bubbling device (3) includes an annular exhaust pipe (302) fixedly installed at the lower end of the outer shell (1). A U-shaped pipe (301) is fixedly communicated with one side of the annular exhaust pipe (302). The upper end of the U-shaped pipe (301) is communicated with the outer cylinder (401).

4. The preparation method of a high-strength, comfortable and durable antibacterial fiber for hotels according to claim 1, characterized in that: The stirring device (2) includes a second motor, a stirring shaft and stirring blades. There are multiple layers of stirring blades. The stirring blades are inclined. The inclination directions of each layer of stirring blades are opposite.

5. The preparation method of a high-strength, comfortable and durable antibacterial fiber for hotels according to claim 1, characterized in that: The rotating shaft (408) includes an upper main shaft (4081) connected to the output shaft of the first motor (403). A lower main shaft (4082) is rotatably installed at the lower end of the upper main shaft (4081). A one-way bearing is arranged between the upper main shaft (4081) and the lower main shaft (4082). The upper main shaft (4081) and the lower main shaft (4082) are rotatably connected to the rotating body (406).

6. The preparation method of a high-strength, comfortable and durable antibacterial fiber for hotels according to claim 5, characterized in that: A slide groove (4061) is provided inside the rotating body (406), and a sliding block (4083) used in conjunction with the slide groove (4061) is fixedly installed on the outer wall of the lower main shaft (4082), and the slide groove (4061) is inclined.

7. The preparation method of a high-strength, comfortable and durable antibacterial fiber for hotels according to claim 1, characterized in that: The following steps are involved: A: Weigh 5g of washed and dried mugwort, crush it, add 50mL of deionized water and 1-1.5mL of ethylenediamine, mix well, and transfer to a polytetrafluoroethylene reactor; B: react in an oven at 150-200°C for 4-15h, cool to room temperature after the reaction, centrifuge, filter insoluble matter, and freeze-dry the solution to obtain brown carbon quantum dot powder; C: Add carbon quantum dots to water to obtain a mass fraction of 2-15% and chitosan to obtain a mass fraction of 30%, mix well and set aside; D: Immerse the core-spun yarn fabric in the above mixed solution, heat to 50-60℃, ultrasonicate for 1-5h, take out the fabric, dry it at 60℃, wash and dry it.

8. The preparation method of a high-strength, comfortable and durable antibacterial fiber for hotels according to claim 7, characterized in that: The core-spun yarn is composed of polyester fiber or iterated polyester as an inner core and cotton fiber or polyester blended or polyester-cotton interwoven fibers covering the outer portion of the inner core.

Citation Information

Patent Citations

  • Preparation method of washable antibacterial nylon composite fabric

    CN117721560A